2022
DOI: 10.1002/asi.24654
|View full text |Cite
|
Sign up to set email alerts
|

Digital divide, critical‐, and crisis‐informatics perspectives on K‐12 emergency remote teaching during the pandemic

Abstract: The rapid deployment of emergency remote teaching in the pandemic presents sweeping societal‐level information systems phenomena worthy of scholarly inquiry. This paper reports findings from teacher interviews conducted with K‐12 public school teachers, exploring how digital access and use gaps in communities reflect wider digital and social inequalities as schools fulfilled emergency remote teaching mandates, becoming swept up into e‐learning technology expansion trends propelled by mandates, and unfettered c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 56 publications
(65 reference statements)
0
9
2
Order By: Relevance
“…Short‐term imposts on behavior included staying at home, social distancing, and wearing masks in public. Long‐term or permanent impacts such as Twitter's Permanent Remote‐Work Policy (Forbes, 2020) are known, but the effect of other policies, such as remote learning by millions of students globally, are largely unknown (Radford et al, 2022; Reynolds et al, 2022).…”
Section: Data Analysis and Findingsmentioning
confidence: 99%
“…Short‐term imposts on behavior included staying at home, social distancing, and wearing masks in public. Long‐term or permanent impacts such as Twitter's Permanent Remote‐Work Policy (Forbes, 2020) are known, but the effect of other policies, such as remote learning by millions of students globally, are largely unknown (Radford et al, 2022; Reynolds et al, 2022).…”
Section: Data Analysis and Findingsmentioning
confidence: 99%
“…The pandemic also highlighted the inequities in the US education system, which give rise to an unequal distribution of technology-supported learning experiences (Aguilar, 2020; Aguiliera and Nightengale-Lee, 2020; Reynolds and Chu, 2020; Reynolds et al , 2022). Compared to children living in higher-income households, children living in low-income households faced disproportionately greater challenges when schools closed down and teaching moved online (Goldhaber et al , 2022).…”
Section: Three Trends In Digital Youth Researchmentioning
confidence: 99%
“…While educational platforms were already established in US educational contexts by the end of the 2010s, the COVID-19 pandemic led to further adoption of – and concern about – these platforms. The pandemic shift to emergency remote teaching (Hodges et al , 2020) across educational institutions required the adoption of new platforms (Greenhow et al , 2021; Pokhrel and Chhetri, 2021), and the urgent nature of the shift likely dissuaded holistic evaluation of these platforms, instead further entrenching utilitarian perspectives of educational technology (see, for example, Reynolds et al , 2022). While long-term educational impacts are yet to be documented, several studies have shown a range of immediate and short-term impacts resulting from the shift from in-person to wholly online education.…”
Section: Introductionmentioning
confidence: 99%
“…In a state-specific study of K-12 level students during COVID-19, DiGiacomo et al (2022a) found that mental health needs increased during online-only schooling, as well as feelings of loss of social connection – again, two critical dimensions of learning. Issues of digital and social inequality also impacted students’ ability to participate in online learning environments during the pandemic, including varying levels of device access and technological skill (Reynolds et al , 2022). Of course, because students learn differently, not all students experienced schooling during COVID-19 in negative ways; the rapid advance in use of a range of online learning technologies also allowed students greater flexibility for engagement in their courses, and many students experienced more autonomy to arrange their schedules (Gonzalez et al , 2020).…”
Section: Introductionmentioning
confidence: 99%